Teddy Dillard

## Answered question

2021-12-17

Find the derivatives of the function y defined implicity by each of the following equation
${x}^{4}+{y}^{4}-{a}^{2}xy=0$

### Answer & Explanation

Thomas Lynn

Beginner2021-12-18Added 28 answers

Step 1
Given
${x}^{4}+{y}^{4}-{a}^{2}xy=0$
Step 2
differentiating wrt "x"
$\frac{d}{dx}\left({x}^{4}\right)+\frac{d}{dx}\left({y}^{4}\right)-{a}^{2}\frac{d}{dx}\left(xy\right)=0$
$4{x}^{3}+4{y}^{3}\frac{dy}{dx}-{a}^{2}\left(x\frac{dy}{dx}+y\cdot 1\right)=0$
$4{x}^{3}+4{y}^{3}\frac{dy}{dx}-{a}^{2}x\frac{dy}{dx}-{a}^{2}y=0$
$\left(4{y}^{3}-{a}^{2}x\right)\frac{dy}{dx}={a}^{2}y-4{x}^{3}$
$\therefore \frac{dy}{dx}=\frac{{a}^{2}y-4{x}^{2}}{4{y}^{3}-{a}^{2}x}$

John Koga

Beginner2021-12-19Added 33 answers

Step 1
In implicit differentiation all the differentiation rules are applicable.
Step 2
${x}^{4}+{y}^{4}-{a}^{2}xy=0$
differentiate both sides wrt x:
$\frac{d}{dx}\left({x}^{4}+{y}^{4}-{a}^{2}xy\right)=\frac{d}{dx}\left(0\right)$
$\frac{d}{dx}\left({x}^{4}\right)+\frac{d}{dx}\left({y}^{4}\right)-{a}^{2}\frac{d}{dx}\left(xy\right)=0$
apply chain rule and product rule of differentiation:
$4{x}^{3}+4{y}^{3}\frac{dy}{dx}-{a}^{2}\left(x\frac{dy}{dx}+y\frac{dx}{dx}\right)=0$
$4{x}^{3}+4{y}^{3}{y}^{\prime }-{a}^{2}\left(x{y}^{\prime }+y\right)=0$
$4{x}^{3}+4{y}^{3}{y}^{\prime }-{a}^{2}x{y}^{\prime }-{a}^{2}y=0$
${y}^{\prime }\left(4{y}^{3}-{a}^{2}x\right)={a}^{2}y-4{x}^{3}$
${y}^{\prime }=\frac{{a}^{2}y-4{x}^{3}}{4{y}^{3}-{a}^{2}x}$
Final answer:
${y}^{\prime }=\frac{{a}^{2}y-4{x}^{3}}{4{y}^{3}-{a}^{2}x}$

Do you have a similar question?

Recalculate according to your conditions!

Ask your question.
Get an expert answer.

Let our experts help you. Answer in as fast as 15 minutes.

Didn't find what you were looking for?